2012
DOI: 10.1158/1940-6207.capr-12-0042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Chronic Obstructive Pulmonary Disease and/or Lung Cancer: Important Considerations When Evaluating Risk

Abstract: Chronic obstructive pulmonary disease (COPD) is defined as a disease causing an airflow limitation that is not fully reversible. COPD is phenotypically complex and characterized by small-airway disease and/or emphysema that result from the interaction between host genetic susceptibility and environmental exposures. As in lung cancer, smoking exposure is the most important risk factor for the development of COPD, accounting for 80% to 90% of all cases. COPD affects an estimated 8% to 10% of the general adult po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…They share a common environmental risk factor in CS exposure and a genetic predisposition (1), as indicated by the fact that 15-30% of smokers developed COPD or lung cancer (2). Fifty to 80% of lung cancer patients have pre-existing COPD, compared with a 15-20% prevalence of COPD in the general smoking population (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…They share a common environmental risk factor in CS exposure and a genetic predisposition (1), as indicated by the fact that 15-30% of smokers developed COPD or lung cancer (2). Fifty to 80% of lung cancer patients have pre-existing COPD, compared with a 15-20% prevalence of COPD in the general smoking population (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is the leading cause of lung cancer (Thorgeirsson et al, 2008). Besides that, some studies have found that genetic factors play an important role in the pathology of LC (El-Zein et al, 2012). It has been demonstrated that caspases are closely related to genetic susceptibility to cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Due to increased habit of smoking these individuals run an increased risk of impaired epithelial barrier function and development of COPD due to increased smoke exposure. The CHRNA3/CHRNA5 locus has also been identified in genome-wide association studies in lung cancer and other diseases significantly influenced by cigarette smoking behavior and exposure [5,6,7].…”
Section: Geneticsmentioning
confidence: 99%